PRESUPPOSITION ANALYSIS IN HEADLINES OF JAKARTA POST NEWSPAPER: A CONTENT ANALYSIS RESEARCH - Syafryadin Syafryadin (Scopus ID 57212212579, WoS ID: ABI-8120-2020) (PROJECT (Professional Journal of English Education), 2022)
Presupposition is one of pragmatics part that should be noticed by everyone because it is essential to know the assumption or interpretation of utterance or written form. Thus, this study aimed to identify the types of presupposition in the headlines of Jakarta Post Newspaper. Qualitative research with content analysis was employed by the researcher to undertake this research.The instrument was a checklist. The corpus was headlines of Jakarta Post Newspaper starting from 1st of February 2022 until 28th of February 2022. The data were analyzed by using several stages namely collecting, reducing, displaying and concluding data. The result showed that five types of presupposition found in headlines of Jakarta Post Newspaper namely existential, lexical, factive, structural, and counterfactual presupposition. The dominant one is existential presupposition. In addition, there is not found non-factive presupposition because the Jakarta Post shows the factual data.